Analisis Pengembangan Sistem Layanan Masyarakat Untuk Pengelolaan Iuran Warga Secara Terintegrasi - Aryantonur, Aryantonur; Darmawan, Hendri; H, Juwita Putri; Maulana, Rijki (Jurnal Sains dan Teknologi (JSIT), 2024)
Neighborhood Association (RT) is the smallest governance system in Indonesia that plays a vital role in population administration and conveying community aspirations to the government. However, the limitations of time and the availability of the RT Chairman often result in administrative services being slow, inefficient, and less responsive to the needs of the residents. Therefore, innovation in the management of administration at the RT level is needed to improve the effectiveness and efficiency of services. This research aims to design and develop a web-based information system that can assist the RT Chairman in managing population data and resident fee payments in a more systematic and organized manner. Currently, fee payments are done manually, with information conveyed through WhatsApp groups, which often causes confusion and difficulties in monitoring payment status. With this information system, residents can independently and transparently monitor their fee payment status and quickly access relevant information. The development of this system uses the Prototyping method, and testing is conducted through white box testing on three main functionalities. The test results show that all paths can be navigated well, although there are warnings when accessed through older browser versions. With this system, it is hoped that RT services will be more efficient, transparent, and easily accessible to residents. This system helps the neighborhood association manage finances and contributions efficiently.